Ficus erecta Thunb. Leaves Ameliorate Cognitive Deficit and Neuronal Damage in a Mouse Model of Amyloid-β-Induced Alzheimer’s Disease - Sohn, Eunjin; Kim, Yu Jin; Kim, Joo-Hwan; Jeong, Soo-Jin (Frontiers in Pharmacology, 2021)
Alzheimer’s disease (AD) pathogenesis is linked to amyloid plaque accumulation, neuronal loss, and brain inflammation. Ficus erecta Thunb. is a food and medicinal plant used to treat inflammatory diseases. Here, we investigated the neuroprotective effects of F. erecta Thunb. against cognitive deficit and neuronal damage in a mouse model of amyloid-β (Aβ)-induced AD. First, we confirmed the inhibitory effects of ethanol extracts of F. erecta (EEFE) leaves on Aβ aggregation in vivo and in vitro. Next, behavioral tests (passive avoidance task and Morris water maze) revealed EEFE markedly improved cognitive impairment in Aβ-injected mice. Furthermore, EEFE reduced neuronal loss and the expression of neuronal nuclei (NeuN), a neuronal marker, in brain tissues of Aβ-injected mice. EEFE significantly reversed Aβ-induced suppression of cAMP response element-binding protein (CREB) phosphorylation and brain-derived neurotrophic factor (BDNF) expression, indicating neuroprotection was mediated by CREB/BDNF signaling. Moreover, EEFE significantly suppressed the inflammatory cytokines IL-1β and TNF-α, and expression of Iba-1, a marker of microglial activation, in brain tissues of Aβ-injected mice, suggesting anti-neuroinflammatory effects. Taken together, EEFE protected against cognitive deficit and neuronal damage in AD-like mice via activation of CREB/BDNF signaling and upregulation of inflammatory cytokines.